Penggunaan Blast Slag Nickel Sebagai Pengganti Agregat Kasar Pada Beton Geopolimer - Mega Paembonan; Frans Phengkarsa; Suryanti Rapang Tonapa (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Geopolymer concrete is concrete that uses polymeric materials as a binder between aggregates. One of the polymer materials is fly ash. Blast slag nickel is waste from industrial plants that produce nickel. In the concrete compressive strength test, the highest test value was obtained at the age of 28 days for the 17,5% variation, which was 33,498 Mpa, for the 15% variation, it was 32,272 Mpa, and for the 0% variation, it was 31,045 Mpa. The split tensile strength test of concrete obtained the highest test value obtained at the 1,.5% variation of 2,972 Mpa, the 15% variation of 2,760 Mpa, and the 0% variation of 2,619 Mpa. Testing the elastic modulus of concrete obtained the highest modulus of elasticity obtained at 17,5% variation of 37287,135 Mpa, 15% variation of 35900,552 Mpa, and 0% variation of 32113,473 Mpa The use of nickel blast slag as a substitute for coarse aggregate and the use of fly ash on geopolymer concrete paste affects the values ​​of compressive strength, split tensile strength, and modulus of elasticity of concrete. Where the more variations of fly ash used, the resulting value of compressive strength, split tensile strength, and modulus of elasticity of concrete increases.